2021
DOI: 10.1002/ijc.33751
|View full text |Cite
|
Sign up to set email alerts
|

Camrelizumab plus oxaliplatin‐based chemotherapy as first‐line therapy for advanced biliary tract cancer: A multicenter, phase 2 trial

Abstract: Biliary tract cancer (BTC) is a highly malignant tumor with limited treatment options and poor prognosis. Our study aimed to evaluate camrelizumab plus oxaliplatin-based chemotherapy as first-line therapy for advanced BTC. In this multicenter, open-label, phase 2 trial conducted in China (ClinicalTrials.gov, NCT03092895), untreated patients with advanced BTC were given camrelizumab (3 mg/kg iv drip injection, every 2 weeks) plus typical FOLFOX4 (Cam-FOLFOX4 group; infusional 5-fluorouracil, leucovorin and oxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…This is the first report on the efficacy and safety of camrelizumab in combination with apatinib in patients with cholangiocarcinoma. Most studies on immunotherapy for advanced biliary tract cancer are in the exploratory stage, and these findings demonstrated promising therapeutic efficacy and relatively manageable toxicity, which needs further trials ( 61 , 62 ).…”
Section: Clinical Efficacy In Liver Cancer and Cholangiocarcinomamentioning
confidence: 99%
“…This is the first report on the efficacy and safety of camrelizumab in combination with apatinib in patients with cholangiocarcinoma. Most studies on immunotherapy for advanced biliary tract cancer are in the exploratory stage, and these findings demonstrated promising therapeutic efficacy and relatively manageable toxicity, which needs further trials ( 61 , 62 ).…”
Section: Clinical Efficacy In Liver Cancer and Cholangiocarcinomamentioning
confidence: 99%
“…BTC patients treated by single ICI displayed dissatisfied ORR ranging from 5.8% to 22% (9, 10). However, recent research of immune-combined therapy in BTC showed an increasing ORR amount to 43.8%~54% (25,26). Whether and how chemotherapy facilitate the anti-PD1 therapy needs exploration.…”
Section: Discussionmentioning
confidence: 99%
“…These promising results suggest that camrelizumab plus oxaliplatin-based chemotherapy could be a new first-line therapy for advanced BTC. 68 Another phase 1 study of durvalumab (an anti-PD-L1) and tremelimumab, an anti-CTLA-4, reported similar, promising results. Durvalumab monotherapy cohorts achieved a median OS of 8.1 months and dual therapy achieved 10.1 months, suggesting its potential as a novel second-line therapy.…”
Section: Ici Combinations and In Synergy With Chemotherapymentioning
confidence: 91%